NK Cells in Autoimmune Diseases: Protective or Pathogenic? - Liu, Meifang; Liang, Shujuan; Zhang, Cai (Frontiers in Immunology, 2021)
Autoimmune diseases are, in general, considered to be a consequence of the loss of self-tolerance (i.e., the immune system fails to distinguish “self” from “non-self”). Autoimmune diseases are commonly characterized by autoantibody production and overactivation of T cells, which eventually leads to tissue damage of specific organs or multiple organs. Hence, autoimmune diseases can be classified into two types: organ-specific and systemic. In general, genetic and environmental factors contribute to the pathogenesis of autoimmunity. More recently, innate immunity has been recognized to participate in the onset of autoimmune diseases. Accumulating evidence has shown that natural killer (NK) cells (key components of innate immune system) participate in the development of diverse types of autoimmune diseases, such as systemic lupus erythematosus, type-I diabetes mellitus and autoimmune liver disease. However, NK cells often have divergent roles in autoimmunity, with protective or accelerating activity in different autoimmune diseases. This paradoxical phenomenon may be associated with the different functional NK-cell subsets, distinct local microenvironments, and different types or stages of autoimmune diseases. In this review, we highlight how NK cells modulate different types of autoimmune diseases. We focus particularly on current understanding of the diversity of NK-cell subsets, their protective or pathogenic roles in systemic and organic-specific autoimmune diseases, and the potential of NK cells as therapeutic targets.